Isolation and structural determination of non-racemic tertiary cathinone derivatives1. Issue 37 (7th October 2015) - Zhou, M.-J.; Bouazzaoui, S.; Jones, L. E.; Goodrich, P.; Bell, S. E. J.; Sheldrake, G. N.; Horton, P. N.; Coles, S. J.; Fletcher, N. C.
<x xml:space="preserve">Abstract</x> In this paper the dynamic resolution of racemic tertiary cathinones is demonstrated through co-crystallization with enantiopure aromatic tartaric acids.